Pengaruh Perubahan BI Rate Terhadap Market Return Dan Volatilitas Indeks LQ45 - Alan Fatih; Fitri Ismiyanti (Universitas Airlangga, 2015)
This study aimed to examine the effect of the announcement of the change in the BI rate to market return and volatility on the index LQ45 during the period March 2010 to February 2015 by using inflation and industrial production index as variable control. This study uses multiple regression analysis (α = 5%). Regression results show that changes in the BI rate has no significant effect on the market return. These results indicate that at the time of the announcement of the BI rate does not give any influence on the market return LQ45. The different results shown by the effect of changes in the BI rate to return volatility LQ45. Volatility increased with the announcement of the increase in the BI rate changes. Furthermore, the control variables, inflation and the industrial production index has no significant effect either on the market returns and volatility of LQ45 so that this control variable can not be used to predict market returns and volatility of LQ45 current BI rate announcement.